DNA and meristic evidence for two species of giant stargazer (Teleostei: Uranoscopidae: Kathetostoma) in New Zealand waters - Peter J. Smith; Robin P. McPhee; Clive D. Roberts (New Zealand Journal of Marine and Freshwater Research, 2006)
The taxonomic status of the banded giant stargazer in New Zealand waters is uncertain. Mitochondrial DNA partial sequences of the cytochrome b gene and the control region, along with three meristic characters (numbers of dorsal fin rays, anal fin rays, and vertebrae), were compared among six recognised species of Kathetostoma and specimens of the banded giant morph. New Zealand specimens referred to as banded giant stargazer were shown to be a discrete species distinguished from the giant stargazer K. giganteum from New Zealand and the banded K. laeve and K. canaster from Australia, by cytochrome b and control region sequences and meristic counts. This undescribed species occurs over a wide geographic range from the Snares shelf (48°S) to the Norfolk Ridge (32°S) in the Tasman Sea, and is largely sympatric with K. giganteum. The two New Zealand species occupy different depth ranges, with the banded giant stargazer generally occurring in shallower water ( K. giganteum (12–1000 m).